New augite geothermometer for nakhlites - Domeneghetti MC; Alvaro M; Fioretti AM; Marinangeli L.; CAMARA ARTIGAS, Fernando (Rendiconti Online della Società Geologica Italiana, 2014)
Nakhlites, together with shergottites and chassinites constitute the “SNC” group of Martian meteorites. MIL 03346 is a nakhlite, that was found at Miller Range, in Antarctica and is mainly composed of clinopyroxene (79%), with minor olivine (1%), and 20% vitrophyric intercumulus material (McBride et al., 2005; Treiman, 2005). The clinopyroxene is augite with a homogeneous core (En36Fs24Wo40) and an iron-enriched rim (En8Fs64Wo28). Since the first modern petrologic studies of Nakhla, the nakhlite group of meteorites has been interpreted as augiterich cumulate igneous rocks, derived from basaltic magma, that erupted onto the surface of Mars (Bunch and Reid, 1975; Reid and Bunch, 1975). However, the relative low closure temperature (Tc) of ca. 500 (±100)°C calculated for MIL 03346 by Domeneghetti et al (2013) with the available geothermometer (Brizi et al, 2000) would imply a slow cooling rate that is in disagreement with the petrologic evidence for an origin from a fast cooled lava flow. Ex-situ annealing experiments combined with high-resolution single-crystal X-ray diffraction (HR-SC-XRD) on crystals from MIL 03346 clearly showed that the degree of order remained unchanged at 600°C thus suggesting that the actual Tc is close to this temperature. Therefore, we undertook an ex situ annealing experiments combined with HR-SCXRD at 600, 700, 800 and 900 °C until the equilibrium in the intracrystalline Fe2+-Mg exchange is reached. The experiments have been performed on two crystals from exactly the same fragment of MIL 03346 sample in order to calibrate a new geothermometer for augites from Martian nakhlites: lnkD = -4421(±561)/T(K) + 1.46(±0.52) (R2=0.988), where kD = [(Fe2+M1)(MgM2) / (Fe2+M2)(MgM1)]. Applying this new equation to MIL 03346 the closure temperature resulted to be 605(84)°C about 100°C higher than that calculated with previously available calibration (i.e. Brizi et al. 2000). However, this closure temperature is still lower than expected based on petrologic evidences and suggests that MIL 03346 ...